2004
DOI: 10.1007/s00264-004-0558-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of wear and osteolysis in hip replacement using two different coatings of the femoral stem

Abstract: We compared the clinical and radiographic results of two matched series of total hip arthroplasties, one with hydroxyapatite-coated femoral stems, the other with a similar but porous-coated femoral stem. The prevalence of radiographic osteolysis was 16% in hips with hydroxyapatite-coated stems and 43% in hips with porous-coated femoral stems. In hips with hydroxyapatitecoated stems, osteolysis was always limited to Gruen zones 1 and 7. In contrast, distal osteolysis was present around 26% of the porous-coated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(21 reference statements)
3
13
1
Order By: Relevance
“…Similarly, a study carried out on HA-coated tapered stems reported a BD decrease in the 1st postoperative year with a recovery at the 3-year follow-up [15]. The present study confirms partial restoration of the postoperative cortical and cancelous BD values in the trochanter and neck region and complete cortical BD restoration in the diaphyseal region.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, a study carried out on HA-coated tapered stems reported a BD decrease in the 1st postoperative year with a recovery at the 3-year follow-up [15]. The present study confirms partial restoration of the postoperative cortical and cancelous BD values in the trochanter and neck region and complete cortical BD restoration in the diaphyseal region.…”
Section: Discussionsupporting
confidence: 77%
“…1,4,5,6 A study carried out on HA-coated tapered stems reported a BMD decrease in the first postoperative year with a recovery at the 3-year follow up. 21 In addition to stress shielding, reduced physical activity in the postoperative period could play a role in this initial bone loss. 1,5 The recovery of BMD values in these studies could be because of the continuing osteointegration process between the bone and implant and better load transfer from the prosthesis to the femoral bone.…”
Section: Discussionmentioning
confidence: 99%
“…250 grey-level thresholding was implemented to differentiate the constituents in the bone/implant surface, where the implant surface was transformed into absolute black (grey level=0.36, bar=300 micrometres). b BSEM images of the simvastatin group sample, demonstrating a greater amount of osseointegration improved bone ingrowth capacity also had preventive effects on osteolysis, which is an important factor for longevity of the implant [21]. Additionally, several local factors have been reported to play a role on osseointegration, including transforming growth factor-B, osteoblasts and autogenous bone graft [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…Although implant design, material and surgical technique were the main factors responsible for the primary stability, biomechanical forces, patient variables and surface coatings affect osseointegration [4]. Several materials have been used in order to accelerate and enhance this process, including surface coatings such as hydroxyapatite-coated implants or experimentally the use of growth factors [4,6,11,19,21].…”
Section: Introductionmentioning
confidence: 99%